Vulnerable Family Members and Income in Chepang Minority - Atreya, Kishor; Rimal, Narayan Sharma; Bhattarai, Sunita; Sapkota, Sujata; Adhikari, Saraswati; Karki, Jiban; Pohl, Gerda (Economic Journal of Development Issues, 2019)
Chepang, an indigenous minority comprising of about 0.26% of Nepal’s population, are ‘highly marginalised’. The presence of vulnerable family members such as single women, people with disability and elderly in the Chepang household may further marginalise them. We used 2019 census data of a rural municipality to estimate farm, non-farm and total incomes in the Chepang households’ and conducted regressions analysis to identify influencing factors, including the effect of the presence of single women, disability and elderly members on household incomes. The study found that Chepang households were mainly engaged in farms, however, the share of non- farm income was significant. On average, a Chepang individual earned US330 per year. Per capita farm income estimated was US120, and that of non-farm was US279. Non-farm income was however constrained by the presence of single women and people with disability. The presence of a single woman caused to reduce non-farm income by 13.4%. Likewise, non-farm income reduced by 20.5% when a Chepang household had disabled member. We suggest further studies on vulnerable members, particularly on their health conditions, and access to government services under the changing social, cultural, and environmental conditions.